Kinetochore assembly and heterochromatin formation occur autonomously in Schizosaccharomyces pombe - Brown, William R.A.; Thomas, Geraint; Lee, Nicholas C.O.; Blythe, Martin; Liti, Gianni; Warringer, Jonas; Loose, Matthew W. (National Academy of Sciences, 2014)
Kinetochores in multicellular eukaryotes are usually associated with heterochromatin. Whether this heterochromatin simply promotes the cohesion necessary for accurate chromosome segregation at cell division or whether it also has a role in kinetochore assembly is unclear. Schizosaccharomyces pombe is an important experimental system for investigating centromere function, but all of the previous work with this species has exploited a single strain or its derivatives. The laboratory strain and most other S. pombe strains contain three chromosomes, but one recently discovered strain, CBS 2777, contains four. We show that the genome of CBS 2777 is related to that of the laboratory strain by a complex chromosome rearrangement. As a result, two of the kinetochores in CBS 2777 contain the central core sequences present in the laboratory strain centromeres, but lack adjacent heterochromatin. The closest block of heterochromatin to these rearranged kinetochores is ∼100 kb away at new telomeres. Despite lacking large amounts of adjacent heterochromatin, the rearranged kinetochores bind CENP-ACnp1 and CENP-CCnp3 in similar quantities and with similar specificities as those of the laboratory strain. The simplest interpretation of this result is that constitutive kinetochore assembly and heterochromatin formation occur autonomously.